2021
DOI: 10.1038/s41598-021-90531-w
|View full text |Cite
|
Sign up to set email alerts
|

Boron from net charge acceptor to donor and its effect on hydrogen uptake by novel Mg-B-electrochemically synthesized reduced graphene oxide

Abstract: Hydrogen uptake (H-uptake) is studied in ball milled Mg-B-electrochemically synthesized reduced graphene oxide (erGO) nanocomposites at PH2 ≈ 15 bar, ~ 320 °C. B/C (weight ratio): 0, ~ 0.09, ~ 0.36, ~ 0.90 are synthesized maintaining erGO≈10wt %. B occupies octahedral interstices within Mg unit cell—revealed by electron density maps. Persistent charge donations from Mg and B to C appear as Mg-C (~ 283.2 eV), B-C (~ 283.3–283.9 eV) interactions in C-1s core X-ray photoelectron spectroscopy (XPS) at all B/C. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The catalytic effects of subsurface carbon on the Mg (0001) surface were explored by ab initio DFT calculations. 93 The Mg−B−erGO nanocomposite was prepared by ball-milling with Mg, B, and electrochemically synthesized reduced graphene oxide (erGO). The authors explained that with a low boron concentration the nanocomposite readily absorbs hydrogen due to the repulsion between B and Mg in the lattice, while a high boron concentration boosts the electron transfer from Mg to B, which causes the lattice to contract and consequently makes hydrogen absorption difficult (Figure 8a).…”
Section: Proposed Mechanisms For Modified Hydrogenmentioning
confidence: 99%
See 3 more Smart Citations
“…The catalytic effects of subsurface carbon on the Mg (0001) surface were explored by ab initio DFT calculations. 93 The Mg−B−erGO nanocomposite was prepared by ball-milling with Mg, B, and electrochemically synthesized reduced graphene oxide (erGO). The authors explained that with a low boron concentration the nanocomposite readily absorbs hydrogen due to the repulsion between B and Mg in the lattice, while a high boron concentration boosts the electron transfer from Mg to B, which causes the lattice to contract and consequently makes hydrogen absorption difficult (Figure 8a).…”
Section: Proposed Mechanisms For Modified Hydrogenmentioning
confidence: 99%
“…The additionally introduced element can influence the interfacial interaction even though it is not directly bonded to the carbon substrate. Aditya et al demonstrated through experiments and calculations that the effect of charge transfer by the interstitial boron on Mg changed with the boron concentration . The Mg–B–erGO nanocomposite was prepared by ball-milling with Mg, B, and electrochemically synthesized reduced graphene oxide (erGO).…”
Section: Role Of Interfacial Interactions In Hydrogen Storagementioning
confidence: 99%
See 2 more Smart Citations
“…NaBH4 [49,74,216,236,241], Mg(BH4)2 [42,55,61,70,105,126,132,151,159,207,216,220,224,236,242,243], Ca(BH4)2 [116,216,236,243] and (TM)(BH4)x [150,216], ammonia-borane NH3.BH3 [36,38,63,64,75,85,86,88,90,139,[140][141][142][143][144]153,154,156,162,171,175,197,213,[244]…”
Section: Tm-hydridesmentioning
confidence: 99%